Technology - based Business Idea Blue Print Automatic Whiteboard Cleaner / Nur Dalila Ja'afar - Ja'afar, Nur Dalila (2020)
Dee’s Whiteboard Company is a small company that will be fully customized for whiteboard necessity. It will provide some useful and needy material like whiteboards, dusters,and also markers. The specialty of this company is it produce and sell a new whiteboard which is an automatic whiteboard cleaner. An automatic whiteboard cleaner can erase the whiteboard by itself. This company also provide maintenance service for the automatic whiteboard cleaner